2015
DOI: 10.1097/qad.0000000000000869
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota diversity predicts immune status in HIV-1 infection

Abstract: Gut microbiota alterations are closely associated with immune dysfunction in HIV-1 patients, and these changes persist during short-term ART. Our data implicate that re-shaping the microbiota may be an adjuvant therapy in patients commencing successful ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
321
8
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(365 citation statements)
references
References 41 publications
29
321
8
7
Order By: Relevance
“…Studies investigating the intestinal microbiome in the setting of HIV-1 infection have used a number of different sequence-based technologies to comprehensively identify and enumerate the constituents of complex, host-associated bacterial communities[37-53]. Although most recent studies used the highly conserved gene encoding the small-subunit ribosomal RNA gene (16S in bacteria/archaea or 18S rRNA in eucaryotes) to infer the types of microorganisms present in a community, the particular hypervariable (V) sub-regions of the 16S gene that were targeted (due to the fact that most next-generation sequencing platforms cannot generate full-length 16S sequences) differed; a number of studies amplified and sequenced the ~250 bp V4 region[37, 40, 42, 43, 53], whereas other studies amplified V1V3[49], V3V4[46, 48, 52], V3V5[39, 50] or V6[47] regions (~530 bp, ~460 bp, ~570 bp, and ~120 bp, respectively). The choice of hypervariable region and particular broad-range primers used for PCR amplification undoubtedly affect the resulting sequence dataset(s) since V regions differ intrinsically in their abilities to resolve phylogeny[24, 54, 55].…”
Section: Microbiome Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Studies investigating the intestinal microbiome in the setting of HIV-1 infection have used a number of different sequence-based technologies to comprehensively identify and enumerate the constituents of complex, host-associated bacterial communities[37-53]. Although most recent studies used the highly conserved gene encoding the small-subunit ribosomal RNA gene (16S in bacteria/archaea or 18S rRNA in eucaryotes) to infer the types of microorganisms present in a community, the particular hypervariable (V) sub-regions of the 16S gene that were targeted (due to the fact that most next-generation sequencing platforms cannot generate full-length 16S sequences) differed; a number of studies amplified and sequenced the ~250 bp V4 region[37, 40, 42, 43, 53], whereas other studies amplified V1V3[49], V3V4[46, 48, 52], V3V5[39, 50] or V6[47] regions (~530 bp, ~460 bp, ~570 bp, and ~120 bp, respectively). The choice of hypervariable region and particular broad-range primers used for PCR amplification undoubtedly affect the resulting sequence dataset(s) since V regions differ intrinsically in their abilities to resolve phylogeny[24, 54, 55].…”
Section: Microbiome Analysismentioning
confidence: 99%
“…Indeed, reductions in diversity have been observed in both untreated and treated HIV-infected subjects compared to uninfected control subjects in mucosal[42, 44] and fecal samples[43, 44, 46, 48]. Surprisingly, bacterial diversity further decreased in stool samples of HIV-1 infected study participants who were followed after the introduction of ART[46] suggesting antiretroviral drugs themselves may impact the intestinal microbiota. Men who have sex with men (MSM) were found to have greater fecal microbial diversity than non-MSM, but HIV-associated reductions in diversity persisted even when HIV-1 infected subjects were stratified for MSM vs. non-MSM[45].…”
Section: Alterations In the Diversity Of Intestinal Bacterial Communimentioning
confidence: 99%
“…22 Of note, we and others have recently shown that HIV-associated changes in gut microbiota are not restored on suppressive ART, providing the rationale for targeting the gut microbiota in treated HIV infection. 18,20,23 Moreover, prebiotic supplementation seemed to increase the percentage of Bifidobacterium and to reduce soluble (s)CD14 levels in HIV-infected patients. 24 Serrano-Villar et al 25 recently reported partly reversed HIVassociated dysbiosis after intervention with prebiotics and glutamine.…”
Section: Introductionmentioning
confidence: 96%
“…Results from a study by Gaardbo et al showed that microberelated effects in the gut are associated with CD4 T-cell loss during HIV-1 infection (35). The dysbiosis that occurs in the gut of HIV-1-infected subjects persisting on ART describes the imbalance of bacterial diversity that is illustrated by increased proinflammatory pathogenic strains (63,64). Importantly, the enhanced tryptophan metabolism related to the composition of the gut microbiota has been linked to the disease progression contributed by enhanced Kyn production in the gut (65).…”
Section: Ccr7mentioning
confidence: 99%